Tingkat Partisipasi Masyarakat dalam Bidang Ekonomi dan Pembangunan Sumber Daya Manusia : Di Kampung Keder Lama Distrik Pantai Timur Bagian Barat Kabupaten Sarmi - Msiren, Rian H.; A. Srem, Ade Irma; Wanma, Johanis R.; Siwa, Siane Florince (Adhigana Papua: Jurnal Ilmiah Magister Manajemen, 2024)
Community participation is a crucial element in the development of human resources (HR) in a region. This study aims to: 1) Identify and analyze the level of community participation in HR development in Keder Lama Village, West Coastal District, Sarmi Regency; and 2) Identify and analyze methods to enhance community participation in improving HR capabilities in the area. This research employs a qualitative approach with a descriptive method. Primary data were obtained through interviews with the Village Head and Community Leaders of Keder Lama Village, while secondary data were sourced from journals and scholarly articles. The findings indicate that the level of economic participation of the Keder Lama Village community in HR development is very good, with active involvement in various activities or training related to enhancing HR capabilities. There are three main methods to improve HR capabilities in Keder Lama Village: tutoring, training, and the opening of job opportunities for the community.